Geochemical compositions of whole rock samples from Lodwar, Turkana County, Kenya - Tanui, F; Olago, D; Ouma, G; Kuria, Z (University of Oxford, 2024)
This study aimed to assess the chemical composition of rocks in Lodwar and its surroundings to understand their potential influence on groundwater quality. A total of 69 rock samples were collected in February and May 2018 during geological mapping and water sampling activities. The samples were analyzed for major oxides, including SiO2, Al2O3, CaO, MgO, Na2O, K2O, TiO2, MnO, Fe2O3, and Loss on Ignition (LOI) using X-ray fluorescence (XRF) at the Department of Mines and Geology in Kenya. Quality control measures for the whole-rock analysis included ensuring that the results of each sample sum to >99.99% or 100%, duplicate sample testing, and calibration of XRF instruments to ensure accuracy and precision. Additionally, the rock samples were carefully georeferenced and packaged under appropriate conditions to avoid contamination during transport and analysis. Related publications: Tanui et al., 2021. Petrography and Geochemistry of the Rocks in Lodwar, Kenya and their Influences on Groundwater Quality. Africa Journal of Physical Sciences Vol 6. pp. 15-44. https://uonjournals.uonbi.ac.ke/ojs/index.php/ajps/article/view/1026/932 (https://ora.ox.ac.uk/objects/uuid:775da78c-a7a7-47bf-b296-9ac5e88948f7)